2010
DOI: 10.1259/bjr/22699201
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis associated with the reversed halo sign on high-resolution CT

Abstract: We describe the case of a 32-year-old woman with pulmonary tuberculosis in whom a high-resolution CT scan demonstrated the reversed halo sign. The diagnosis of tuberculosis was made by lung biopsy and the detection of acid-fast bacilli in the sputum smear and culture. Follow-up assessment revealed a significant improvement in the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Additional findings included centrilobular nodules and subcarinal and left hilar lymphadenopathy [16]. In another case of tuberculosis with the RHS in an adult female, the associated CT findings included pulmonary nodules and areas of consolidation with cavitation [17]. A peculiarity reported in a patient with active tuberculosis and the RHS, and also mentioned in other granulomatous infectious processes including schistosomiasis and cryptococcosis, is the nodular appearance of the ring in the RHS, which has been histologically proven to correlate to granulomas, therefore assisting in the differentiation of active granulomatous disease vs organising pneumonia ( Figure 4) [12,18].…”
Section: Tuberculosismentioning
confidence: 99%
“…Additional findings included centrilobular nodules and subcarinal and left hilar lymphadenopathy [16]. In another case of tuberculosis with the RHS in an adult female, the associated CT findings included pulmonary nodules and areas of consolidation with cavitation [17]. A peculiarity reported in a patient with active tuberculosis and the RHS, and also mentioned in other granulomatous infectious processes including schistosomiasis and cryptococcosis, is the nodular appearance of the ring in the RHS, which has been histologically proven to correlate to granulomas, therefore assisting in the differentiation of active granulomatous disease vs organising pneumonia ( Figure 4) [12,18].…”
Section: Tuberculosismentioning
confidence: 99%
“…However, subsequent studies with pathologic confirmation have shown that the RHS is caused in most cases by the presence of non-necrotizing granulomas [11,28]. Two initial case reports described the RHS in patients with tuberculosis [29,30]; both had anatomopathologic confirmation showing multiple caseating granulomas and positive cultures for Mycobacterium tuberculosis. Recently, a study comparing 12 cases of the RHS in patients with tuberculosis and 10 in patients with COP [31] showed that all patients with tuberculosis presented the RHS with nodular walls and that small nodules were also observed inside the ground-glass component of the RHS in 83 % of these cases.…”
Section: Organizing Pneumoniamentioning
confidence: 99%
“…Questo segno è molto suggestivo di polmonite in organizzazione (PO) ed ha elevata specificità per questa diagnosi, anche se è stato rilevato solo in un quinto dei pazienti con tale patologia [32][33][34][35]. Altre malattie polmonari possono essere associate a componenti significative di PO e il RHS è stato recentemente descritto in altre condizioni, quali zigomicosi polmonare [36,37], la vasculite dei piccoli vasi polmonari [38], la granulomatosi di Wegener [39], la granulomatosi linfomatoide [40], la sarcoidosi [41,42], la tubercolosi polmonare [43,44]. Considerando il numero di pazienti esaminati, questo segno sembra essere rilevante nella polmonite da influenza A (H1N1).…”
Section: Fig 7abunclassified